Phage therapy for Clostridioides difficile infection - Fujimoto, Kosuke; Uematsu, Satoshi (Frontiers in Immunology, 2022)
Clostridioides difficile is endemic in the intestinal tract of healthy people. However, it is responsible for many healthcare-associated infections, such as nosocomial diarrhea following antibiotic treatment. Importantly, there have been cases of unsuccessful treatment and relapse related to the emergence of highly virulent strains of C. difficile and resistance to antimicrobial agents. Fecal microbiota transplantation (FMT) is considered an effective therapy for recurrent C. difficile infection. However, its safety is of concern because deaths caused by antibiotic-resistant bacterial infections after FMT were reported. Therefore, the development of effective C. difficile-specific treatments is urgently needed. In this review, we summarize the importance of phage therapy against C. difficile, and describe a novel next-generation phage therapy developed using metagenomic data.